The Use Of A QR Code On A Notary Deed Is A Manifestation Of The Obligations Of A Notary Under The Law - Nugrahaningsih, Widi; R, Agusta Pinta Kurnia (VJJ, 2020)
The rampant fraud in society, especially the existence of parties claiming to be notaries (being fake notaries) and making deeds occur in the community and are very disturbing, have occurred in several areas, one of which is in Sleman. The problem that is taken from this research is whether the benefits of using Quick Response code (QR code) in making a notary deed? The purpose of this research is to find out information about the benefits of QR codes in making notarial deeds in order to provide security guarantees for the parties in the notarial deed. The research method is descriptive and explanatory research, the research approach used is empirical, the types and sources of data from primary and secondary data. While the data collection technique is by means of interviews (interviews with notaries who have used the QR code on the deed they have made), direct observation (by looking at the forms or models of deeds made) and literature study. Data collection techniques with data reduction steps, data presentation, drawing conclusions. The conclusion from the research is that the use of QR Code in making notarial deeds does not violate the provisions of the Law, even in accordance with Article 16 paragraph (1) letter g UUJN-P, that notaries are obliged to act honestly, thoroughly, independently, not taking sides, and protecting interests. the parties involved in legal action.